회전식 통풍관 생물반응기로부터 생산된 느타리균의 다목적 과산화효소(VP) 정제 및 특성 - 하효철 (Journal of mushrooms, 2023)
In this study, Pleurotus ostreatus No.42 was cultured in glucose-peptone-yeast-wheat bran medium using a previously reported novel rotary draft tube bioreactor. Versatile peroxidase (VP), a lignin-degrading enzyme, was isolated from a pellet-type mycelium culture grown in the medium for seven days. The VP was purified by sequentially applying ultra-filtration, DEAESepharose CL-6B column, and Mono Q column. SDS-PAGE analysis revealed the molecular weight of VP to be 36.4 KDa with an isoelectric point of 3.65. The amino acid sequence was confirmed as VTCATGQTT. The purified VP was observed to possess the property of not only oxidizing Mn ions but also decomposing veratryl alcohol, a non-phenolic compound. The catalytic ability of VP is a subject for future research.